1988
DOI: 10.1128/iai.56.4.993-997.1988
|View full text |Cite
|
Sign up to set email alerts
|

Antiheart antibody-dependent cytotoxicity in the sera of mice chronically infected with Trypanosoma cruzi

Abstract: Sera of mice chronically infected with Trypanosoma cruzi contain antibodies that bind to the surface of living adult syngeneic heart muscle cells. In a syngeneic system, with nonadherent spleen mononuclear cells as effector cells and cardiocytes as targets, antibody-dependent cytotoxicity (ADCC), revealed by the liberation of creatine phosphokinase from damaged cardiocytes, was observed after incorporation of serum samples from infected mice. Target damage was decreased after absorption with syngeneic myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…Serum samples were diluted 1:1,000, incubated with increasing concentrations of conjugated peptide R-13 (O), R-10 (A), R-7 (O), or AEAELVKMALMKV (@), and assayed for binding to JL5 fusion protein. 16,19,23), may operate alone or in association and may contribute to generate the chagasic anti-P response.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…Serum samples were diluted 1:1,000, incubated with increasing concentrations of conjugated peptide R-13 (O), R-10 (A), R-7 (O), or AEAELVKMALMKV (@), and assayed for binding to JL5 fusion protein. 16,19,23), may operate alone or in association and may contribute to generate the chagasic anti-P response.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…Numerous reports demonstrated the presence of autoantibodies in parasite-infected hosts. In some studies, it has been shown that autoantibodies found in parasite-infected hosts recognize not only normal tissue but the infected parasite itself (Khoury et al 1979, Szarfman et al 1982, Said et al 1985, Laguens, Meckert & Chambo 1988, Van Voorhis & Eisen 1989, Ternynck et al 1990, Ternynck et al 1991). However, it was not known whether these autoantibodies recognize antigenic determinants cross-reactive with autologous or heterologous parasite antigens such as demonstrated in this study.…”
Section: The Effect Of Proteolytic Enzymes or Periodate Treatment On mentioning
confidence: 99%
“…1991). On the other hand, autoantibodies cross reactive with parasites have been reported with T. cruzi (Szarfman et al 1982, Snary et al 1983, Said et al 1985, Laguens, Meckert & Chambo 1988, Van Voorhis & Eisen 1989. These phenomena are interesting in two respects.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Antibodies directed at parasite antigens are known to induce the lysis of cells infected with various viruses (11,14,28), Coxiella sp. (17), and protozoa (18,22,27) by the action of antibody and complement and/or antibody-dependent cellular cytotoxicity (ADCC). Despite binding to infected cells, however, antibodies to chlamydial genus-specific lipopolysaccharide antigen on the surface did not induce complement-mediated cytolysis (15), and ADCC was not examined.…”
mentioning
confidence: 99%